Keep calm, teach on : education responding to a pandemic - Vyortkina, Dina; Collins, Neil; Reagan, Timothy G. (International perspectives on educational policy, research, and practice., 2022)
"COVID-19 has had massive social, political, and economic consequences, not least in education. Schools and universities globally closed their doors and sought to provide educational services to students in other, alternative ways. This book is a collection of essays about how different institutions and systems of education around the world have attempted to meet the challenges created by COVID-19. It reports the impact of the pandemic in both developed and developing nations and at all levels of education. The collective responses and lessons learned are analyzed to explain the relative success of different coping strategies"--